PENGARUH EFISIENSI TERHADAP EFEKTIFITAS PENGELOLAAN KEARSIPAN PADA BAGIAN UMUM BADAN PENDAPATAN DEARAH KABUPATEN KUTAI BARAT - Kristina Natalia (ADMINISTRASI PUBLIK, 2020)
The Population and Civil Registration Office of West Kutai Regency is one of the district level SKPDs that conduct public services. In accordance with its functions, namely managing archives (documents) and population administration data, the Department of Population and Civil Registration performs duties on the services of the West Kutai community in terms of archival storage and population administration data in the West Kutai District area.In conducting public services, every employee in the Office of Writing and Civil Registration must be guided by the principles of good governance, including in Law No. 23 of 2014, namely: legal certainty, public order, general interest, openness, proportionality,professionalism, accountability, efficiency, effectiveness and justice. Efficiency in the principle of administration that is oriented towards minimizing the use of resources to find the best work results.The research objectives are: 1) Identifying activities in the environment of the Population and Civil Registration Office of West Kutai Regency that are efficient. 2) Knowing how the effectiveness of archival management affects the Population and Civil Registration Office of West Kutai Regency.This research is an export type using quantitative data. Research conducted by the author is a verification or causality research. The randomly selected samples were 25 respondents. Analysis tool using the Spearman Rank coefficient ( ).From the results of the search for rs at n = 25 and α = obtained rs table = 0.425. If rs comparison with rs table will get results rs> rs table; means that Ho is rejected; meaning that efficiency is associated with effectiveness. It can be concluded that: 1) The existence of an efficient relationship with the effectiveness of work in the environment of the Population and Civil Registration Office of West Kutai Regency. 2) Employees in the Department of Population and Civil Registration of West Kutai Regency can receive efficiency measures carried out, even though it is necessary to ensure that the benefits of the efficiency are carried out.